1971
DOI: 10.2323/jgam.17.51
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Dissimilation of Glucose by Heterolactic Bacteria

Abstract: The studies were made on the reduced pyridine nucleotide-oxidizing enzymes in heterolactic bacterium, Leuconostoc mesenteroides IFO 3426, and it was confirmed that both NADH9 oxidase and NTADPH2 oxidase were found in the supernatant fraction prepared by ultracentrifugation at 105,000 x g for 2 hr. The purification and basal properties of these enzymes were described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1971
1971
1996
1996

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Although activities of NADH2 oxidase and NADPH2 oxidase were detected in the organism (9), it was previously reported that lactic acid formation by this organism was hardly affected by oxygen, while, under aerobic conditions, ethonol production decreased with a corresponding increase in acetate production indicating the existence of some mechanism of specific protection of lactic acid-forming system against the effect of oxygen ( 8 ). It is very interesting that ALDH and ADH of the organism were detected as insoluble enzymes suggesting the possibility of different localization of lactic acid dehydrogenase and glyceraldehyde 3-phosphate dehydrogenase from ALDH, ADH, NADH2 oxidase or NADPH2 oxidase.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although activities of NADH2 oxidase and NADPH2 oxidase were detected in the organism (9), it was previously reported that lactic acid formation by this organism was hardly affected by oxygen, while, under aerobic conditions, ethonol production decreased with a corresponding increase in acetate production indicating the existence of some mechanism of specific protection of lactic acid-forming system against the effect of oxygen ( 8 ). It is very interesting that ALDH and ADH of the organism were detected as insoluble enzymes suggesting the possibility of different localization of lactic acid dehydrogenase and glyceraldehyde 3-phosphate dehydrogenase from ALDH, ADH, NADH2 oxidase or NADPH2 oxidase.…”
Section: Discussionmentioning
confidence: 95%
“…mesenteroides IFO 3426 was used throughout this study and procedures for cultivation and preparation of washed cells were the same as previously reported ( 9).…”
Section: Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, inconvenient that pre-aeration of washed cells of L. buchneri without addition of glucose did not induce anaerobic dissimilation of glucose, whereas they possess both NADH2 and NADPH2 oxidases similar to those from Leuconostoc mesenteroides ( 22 ). Moreover, the most of intracellular pyridine nucleotide coenzymes were found to be in oxidized form in the washed cells just before their use in the experiments (unpublished results).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, NADH2 oxidase and NADPH2 oxidase were partially purified from this organism, and basic characteristics of these oxidases were previously reported (9).…”
mentioning
confidence: 84%